Is Pasture Cropping a Valid Weed Management Tool? - Luna, Ignacio Martin; Fernández-Quintanilla, César; Dorado, José (MDPI, 2020)
The aim of the present work was to study the feasibility of pasture cropping under the Mediterranean conditions prevailing in central Spain and its potential as a weed management tool. Three cropping systems were assessed: conventionally grown winter barley and winter barley in pasture cropping with two perennial summer species, Cynodon dactylon and Eragrostis curvula. The results showed that the growth of these two species in a pasture cropping system was limited by the severe drought conditions and high temperatures present during the summer in some of the study years. Although there were no differences in the establishment of winter barley in any of the treatments assessed, pasture cropping reduced winter barley yields up to 50%–60% in years with low rainfall in spring. Regarding weed control, pasture cropping showed a significant suppression of the total weed density and number of weed species. As a conclusion, pasture cropping can be considered as a valid weed management tool. However, the economic feasibility of this system under the climatic conditions of central Spain (characterized by a high risk of severe summer droughts) is still not clear. The availability of supplemental irrigation may reduce competition between pastures and winter crops and ensure a profitable production of summer pastures.